Liquidity crises in emerging markets: Theory and policy - Roberto Chang; Andres Velasco (Federal Reserve Bank of Atlanta, 1999)
We build a model of financial sector illiquidity in an open economy. Illiquidity is defined as a situation in which a country's consolidated financial system has potential short-term obligations that exceed the amount of foreign currency available on short notice. We show that illiquidity is key in the generation of self-fulfilling bank and/or currency crises. We discuss the policy implications of the model and study issues associated with capital inflows and the maturity of external debt, the role of real exchange depreciation, options for financial regulation, fiscal policy, and exchange rate regimes.
Keywords: 330; Financial crises; Foreign exchange; Capital movements; Liquidity (Economics)